Optimalisasi Layanan Informasi Sebagai Upaya Preventif Bahaya Narkoba Bagi Naposo Nauli Bulung Desa Bonan Dolok: Penelitian - Asmaryadi; Saifuddin Bandaharo; Yusmiati; Fauzan Habibie; Andes Fuady Dharma; Ahmad Zaki (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research uses a qualitative descriptive approach involving written sentences, individuals, and observed actions.The data for this research was collected through data triangulation techniques, which combine various data sources through observation and unstructured interview methods.One of the causes of low awareness of the dangers of drugs is the lack of access to structured and interesting information. In contrast, trust in information from traditional or local leaders suggests that there is a high likelihood that conventional communication methods can be optimized for prevention efforts. The information services provided have given Naposo Nauli Bulung a better understanding of the effects of drugs, which include physical, mental, and social damage. This research explains that information services are a very important tool to prevent the dangers of drugs for Naposo Nauli Bulung in Bonan Dolok Village. Appropriate and sustainable information can increase knowledge, awareness and anti-drug attitudes among youth. This information not only motivates people to change their behavior, but also encourages social awareness and active participation in building a healthy and drug-free environment.